PENGARUH IKLAN SABUN MANDI DI TELEVISI TERHADAP PERUBAHAN PERILAKU SISWA KELAS VII SLTP SULUH JAKARTA - Eko Purnomo (Populis : Jurnal Sosial dan Humaniora, 2018)
The development of advertisement in Indonesian television media is quite fast considering the growth of electronic media also penetrated in Indonesia, the television media advertising producers do not want to miss and want to continue to be accepted in the community. Today, people especially in Indonesia are smarter in choosing what they need, therefore, the producers are competing to perform activities that are unique and interesting to keep consumers hearted.               The formulation of the problem in this research is the influence of television advertisement advertisement of lifebuoy soap to behavior change hence the purpose of this research is, to see the influence of television advertisement advertisement to the behavior change of Grade VII student of SLTP Suluh Jakarta.The theoretical framework used in the study consists of Stimulus Theory, response organism, social learning theory and also the Hierarchy of Effect model as the basis of the difference in the effect of behavior change of each individual in seeing something that interest him.               This research is quantitative daskriptif, which aims to spread the situation or various events, and the data obtained from the population that is the students of SLTP Suluh sejumalah 56 respondents, sampling using proportional sampling which is part of probability sampling.               Based on the result of the research, the respondents of Grade VII students of SLTP Suluh Jakarta who tend to have male gender (62.5%), health soap users (53.6%) who get pocket money ≥ 300.000 per month (62.5%) that influence ad impressions television lifebuoy to behavior change Student of SLTP Suluh Jakarta is the influence of change of behavior strongly low, and influential equal to (52,5%).Keywords: Growth of electronic media, behavior change and advertising influence.